PROSES PENYELENGGARAAN PEMILIHAN KEPALA DESA DALAM PERGANTIAN ANTAR WAKTU DI DESA TALUMAE KECAMATAN WATANG SIDENRENG - K, Muh. Arif Rezki Ananda; Irwan; B, Sofyan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to find out how the Village Head Election Process is held during Inter-Time Changes in Talumae Village, Watang Sidenreng District. This research uses descriptive qualitative methods. Participants were selected using a purposive sampling technique with 7 informants as data sources. The data collection techniques used were observation, interviews, and documentation with data processing and analysis techniques using Nvivo 12 software. The results of the research show, This research found that the process of selecting village heads over time in Talumae Village succeeded in implementing the principles of local democracy in depth. . The results of the analysis show that the two main dimensions of democracy according to Robert Dahl, namely liberalization (through open and competitive public contestation) and inclusiveness (with broad participation from various levels of society), are implemented well. Actors such as the Chair of the Village BPD, the PAW Village Election Implementation Committee, the District Head, and the Village Government are actively involved in ensuring political freedom without discrimination and equal participation, building legitimacy and public trust in the election process. High transparency in each stage also increases public monitoring and legitimacy of election results.